(untitled) (African Journal of Biomedical Research, 2022)
Kidney disease (KD) is one of the major public health threats with rising incidence and prevalence rates. Knowledge and perceived risk increase the perception of being susceptible, leading to adoption of behavioural modifications. The objective was to evaluate the knowledge of KD risk factors and perceived susceptibility as well as predictors of KD risk in Lagos State, Nigeria. This was a cross-sectional study conducted in Lagos State, South-western Nigeria. A pretested structured questionnaire was used to draw information from 1171 male and female residents aged ≥ 18 years on socio-demography, knowledge and perceived susceptibility to KD risk. Percentages, frequencies, Chi-square, binary and multinomial logistic regression models were used, with a significance of p<0.05. A total of 1,061 participants, with a mean age of 33.8±11.5 years and male-female ratio of 1.2:1, completed the instrument. Only 78.6% had good knowledge of KD risk factors, while 63.0% had perceived low susceptibility to KD risk. The common self-reported risk factors were high salt intake (91.28%) and herbal concoction (82.21%). High blood pressure (17.51%), high blood sugar (17.96%) and family history of KD (7.92%) were also self-reported. The independent predictors of KD risk were herbal concoction [OR=3.43, CI=1.88‒6.27] and frequent use of pain killers [OR=2.06, CI=1.24‒3.39]. Knowledge of KD risk factors was quite high but perceived susceptibility to KD risk was low. There is a need for continuous sensitization, educational health interventions and screening for early detection.